Splenic Artery Embolisation for the Emergency Treatment of Sinistral Portal Hypertension: A Systematic Review - Harriet Grout-Smith; Ozbil Dumenci; N. Paul Tait; Ali Alsafi (Journal of Clinical Interventional Radiology ISVIR)
Objectives Sinistral portal hypertension (SPH) is caused by increased pressure on the left portal system secondary to splenic vein stenosis or occlusion and may lead to gastric varices. The definitive management of SPH is splenectomy, but this is associated with significant mortality and morbidity in the acute setting. In this systematic review, we investigated the efficacy and safety of splenic artery embolisation (SAE) in managing refractory variceal bleeding in patients with SPH. Methods A comprehensive literature search was conducted using MEDLINE and Embase databases. A qualitative analysis was chosen due to heterogeneity of the studies. Results Our search yielded 339 articles, 278 of which were unique. After initial screening, 16 articles relevant to our search remained for full text review. Of these, 7 were included in the systematic review. All 7 papers were observational, 6 were retrospective. Between them they described 29 SAE procedures to control variceal bleeding. The technical success rate was 100% and there were no cases of rebleeding during follow up. The most common complication was post-embolisation syndrome. Four major complications occurred, two resulting in death. These deaths were the only 30-day mortalities recorded and were in patients with extensive comorbidities. Conclusions Although there is a distinct lack of randomized controlled studies comparing SAE to other treatment modalities, it appears to be safe and effective in treating hemorrhage secondary to SPH.